Arguing Dialogically: Engagement Resources Used in an Indonesian Senior Secondary EFL Textbook - Yonata, Fadhila; Prastikawati, Entika Fani (Universitas Negeri Semarang, 2022)
The current study aims to disclose how arguments of writer and sources of other voices are generated in the pedagogical-proposed texts in the textbook under appraisal analysis. While a plethora of studies on evaluation of interpersonal linguistic features or Engagement resources used in students’ writings in tertiary context, little studies focus on senior secondary level. To fill this niche, this study investigates Engagement resources of expository text in Indonesian mandatory EFL textbook which is used as model or sample for writing section. Students in this level may not be expected to produce good arguments since they are actually in progress to learn how to articulate their ideas through certain genres. Considering this condition in mind, the sample or model text used in the classroom is crucial. Following appraisal framework (Martin White, 2005), two exposition texts are generated as source data in attempt to investigate linguistic features and strategy of the textual voice in expressing authorial or external voices. The findings suggest the needs of evaluation of text provided in textbook from the lens of appraisal analysis as an alternative and it is also recommended for teachers as facilitator in writing exposition text to overtly take Engagement resources into account in teaching process in order to facilitate students’ writing with intertextuality.